MEDIA PEMBELAJARAN BERBASIS PERTANIAN INDUSTRIAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI KEGIATAN EKONOMI - Widyawat, Wike; Sulthon, Ilma Kamila; Sudarti, Sudarti; Wuryaningrum, Rusdhiyanti (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Science learning has an important role in equipping students to be more sensitive to the social problems around them. Students' critical thinking needs to emerge inlearning so that they are able to see things from various sides. This research aims to develop audiovisual-based learning media in the form of agricultural industry-based learning videos on IPAS material, namely